Antitrust perspectives for durable-goods markets - Michael Waldman (Center for Economic Studies and ifo Institute (CESifo), 2004)
Markets for durable goods constitute an important part of the economy. In this paper I first briefly review the microeconomic theory literature on durable-goods markets, focusing mostly on the last ten years. I then discuss a number of my own recent analyses concerning optimal antitrust policy in durable-goods markets that mostly build on ideas in the larger literature. Specific topics covered include: (i) optimal antitrust policy for durable-goods mergers; (ii) practices that eliminate secondhand markets; (iii) tying in markets characterized by upgrades and switching costs; and (iv) antitrust policy for aftermarket monopolization in durable-goods markets.
Keywords: L40; 330; Konzentrationspolitik; Dauerhaftes Konsumgut; Mikroökonomik